2019
DOI: 10.1039/c9em00193j
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the distribution of microfiber pollution in a southern Lake Michigan watershed through the analysis of water, sediment and air

Abstract: Microplastic waste is a worldwide problem, heavily afflicting marine and freshwater environments; the loading of this pollution in water, sediment and living organisms continues to escalate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…3b and 4), dominating the color blue (42 %), followed by the color black (37 %). These results are in agreement with other MPs studies where blue and black colors prevailed in MPs samples (Duncan et al, 2018;Wang et al, 2018;Peller et al, 2019;Alfonso et al, 2020). Also, we found that a considerable part of the blue and black fibers found in the lakes was associated with the Indigo Blue dye related to synthetic textiles, one of the common sources of microfibers (MFs) in aquatic systems.…”
Section: Microplastics Classification and Identificationsupporting
confidence: 93%
“…3b and 4), dominating the color blue (42 %), followed by the color black (37 %). These results are in agreement with other MPs studies where blue and black colors prevailed in MPs samples (Duncan et al, 2018;Wang et al, 2018;Peller et al, 2019;Alfonso et al, 2020). Also, we found that a considerable part of the blue and black fibers found in the lakes was associated with the Indigo Blue dye related to synthetic textiles, one of the common sources of microfibers (MFs) in aquatic systems.…”
Section: Microplastics Classification and Identificationsupporting
confidence: 93%
“…In fact, it has been suggested that sedimentation of fMPs occurs in river sediments [63]. Coastal sediments are also accumulation sites of fMPs [64]. Based on our results, freshwater sediments have reasonably been shown to be fMP sinks.…”
Section: Microplastics In Water and Sedimentsupporting
confidence: 67%
“…This method was originally applied to wastewater to remove organic matter and contaminants (Kuo, 1992) and has been applied in microfiber studies since 2013 (Faure et al, 2015). The few studies that have used this method have shown that it can degrade cellulose (Peller et al, 2019) or cause discoloration and breakage in cotton and rayon (Wiggin & Holland, 2019). Incubation in Fenton reagent can also cause iron deposits on viscose and cotton (Treilles et al, 2020).…”
Section: Methods For Extraction and Characterization Of Microfibersmentioning
confidence: 99%